Pengukuran Keterampilan Berpikir Tingkat Tinggi Mahasiswa Menggunakan Level Hots Marzano - Trisnawaty, Wulan; Salamah, Evi Rizqy; Qorimah, Esti Nur; Tiyas Rifayanti, Zuni Eka (Wahana Sekolah Dasar, 2024)
This was survey research which aims to measure the higher order thinking skills of students at STKIP PGRI Pacitan. Respondent of this research were student of PGSD Department at STKIP PGRI Pacitan which total of 34 respondens. From the survey results obtained that of the 13 Marzano HOTS levels, not a single level was in the high category. Apart from that, there were only 3 Marzano HOTS levels which are in the moderate category, namely the level of comparing, classifying, and deductive reasoning. Meanwhile, the 10 levels other, namely inductive reasoning, analyzing errors, constructing support, analyzing perspective, abstracting, decision making, investigation, problem solving, experimental inquiry, and invention are in the low category. In this way, this research can measure students' cognitive levels so that they can be given appropriate treatment to improve their higher order thinking skills.